Kelarutan Methyl Red dan Methylen Blue dalam Gelasi Mikroemulsi Water in Oil Sistem dari Air, Triton X-100 dan Sikloheksana Serta Aplikasinya Untuk Tinta Ballpoint - Ali Amran, Nurul Khasyi’ah, Ananda Putra, (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
The solubility of methyl red and methylene blue in the gelation of water in oilmicroemulsion of the system of water (pH=4,0 dan pH= 9,5),Triton X-100, cyclohexaneand its application for ballpoint ink. To get the stable red colour of methyl red we used thewater pH 4,0 (controlled by nitric acid) and to get the stable blue colour of methylen blue,we used the water pH of 9,5 (controlled by potassium hydroxide), the formation of gel fromwater in oil microemulsion was crieddent using the sol-gel method byTetraethylorthosilicate (TEOS) which underwent hydrolysis with water to form a gel. Itwas indicated that the solubility of methyl red and methylen blue The gelation of water inoil microemulsion were 1.6820 gram and 1,7260 gram.Keywords: Solubility, methyl red, methylene blue, gel, water in oil icroemulsion,ballpoint ink.